Supplemental feeding of a gut microbial metabolite of linoleic acid, 10-hydroxy-cis-12-octadecenoic acid, alleviates spontaneous atopic dermatitis and modulates intestinal microbiota in NC/nga mice. (17th November 2017) - Kaikiri, Hiroko; Miyamoto, Junki; Kawakami, Takahiro; Park, Si-Bum; Kitamura, Nahoko; Kishino, Shigenobu; Yonejima, Yasunori; Hisa, Keiko; Watanabe, Jun; Ogita, Tasuku; Ogawa, Jun; Tanabe, Soichi; et al.
Abstract: The present study investigated the antiallergic and anti-inflammatory effects of 10-hydroxy- cis -12-octadecenoic acid (HYA), a novel gut microbial metabolite of linoleic acid, in NC/Nga mice, a model of atopic dermatitis (AD). Feeding HYA decreased the plasma immunoglobulin E level and skin infiltration of mast cells with a concomitant decrease in dermatitis score. HYA feeding decreased TNF-α and increased claudin-1, a tight junction protein, levels in the mouse skin. Cytokine expression levels in the skin and intestinal Peyer's patches cells suggested that HYA improved the Th1/Th2 balance in mice. Immunoglobulin A concentration in the feces of the HYA-fed mice was approximately four times higher than that in the control mice. Finally, denaturing gradient gel electrophoresis of the PCR-amplified 16 S rRNA gene of fecal microbes indicated the modification of microbiota by HYA. Taken together, the alterations in the intestinal microbiota might be, at least in part, associated with the antiallergic effect of HYA. Graphical Abstract: